2007
DOI: 10.1017/s0021932006001556
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Socioeconomic Status, Allostatic Load and Measures of Health in Older Taiwanese Persons: Taiwan Social Environment and Biomarkers of Aging Study

Abstract: SummaryData from a national representative sample of 1023 elderly and near-elderly Taiwanese were used to explore whether allostatic load is associated with health outcomes and mediates the association between socioeconomic status and health in a non-Western population. The information collected included: demographic characteristics; allostatic load scores; socioeconomic status, measured by education and income; health behaviours; health-related variables, including self-rated health, basic activities of daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 49 publications
7
48
1
Order By: Relevance
“…Women abstaining from alcohol were also at increased risk of high AL. However, individuals might restrain from alcohol consumption due to medical conditions or other reasons such as past drinking (Gallo et al, 2011;Hu et al, 2007). Consistently with previous research showing the beneficial effects of physical activity on various physiological processes (Warburton et al, 2006), we found that men and women reporting high physical activity had lower AL and lower dysregulation of several physiological axes including metabolism, cardiovascular axis, lipidic profile and oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Women abstaining from alcohol were also at increased risk of high AL. However, individuals might restrain from alcohol consumption due to medical conditions or other reasons such as past drinking (Gallo et al, 2011;Hu et al, 2007). Consistently with previous research showing the beneficial effects of physical activity on various physiological processes (Warburton et al, 2006), we found that men and women reporting high physical activity had lower AL and lower dysregulation of several physiological axes including metabolism, cardiovascular axis, lipidic profile and oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the research that has investigated determinants of AL in Western populations, several studies have also been conducted in Asian countries such as Japan, Taiwan or Nepal, and may therefore provide an interesting ethnic or cultural contrast for the study of determinants of AL (Hu et al, 2007;Kusano et al, 2015;Worthman and Panter-Brick, 2008). Kusano et al (2015) have shown that in elderly Japanese, high alcohol intake was associated with high AL, and increased vegetable consumption was associated with lower AL, a tendency which was also observed in our study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations